Potentials of Local Economic Development in Aspect of Tourism - Viktória Csizmadiáné Czuppon; Edina Sáriné Csajka; Tamás Molnár (DETUROPE)
The objective of the study is to introduce the potentials of local economic development in one of the least favoured micro regions, Tamási. The paper examines operating and planned activities at settlements of the micro region. The authors introduce local economic development activities that support tourism. The economic development planning in Tamási micro region has typically two directions. One of them is the utilisation of thermal water and the use of further potentials of the thermal bath (Ability), such as to achieve tourism destination function in Hungary. Secondly, the local government aims to sell its fruits and vegetables produced in the frame of public employment programme for local market and institutions. The supply of local population has got in focus because of current external opportunities (or force?) in the settlements being traditionally agricultural area. The objective is to join the local tourism attractions and destinations with other existing local developments, which is hold back by the owners of developments. The authors – by keeping in mind local conditions and endogenous resources – define recommendations for settlements to be able to create a well-organised framework of local economic development.